Cutout reinforcements for shear loaded laminate and sandwich composite panels - Guo, Shijun J.; Zhou, L.; Cheung, C. W. (Springer Science Business Media, 2008)
This paper presents the numerical and experimental studies of shear loaded laminated and sandwich carbon/epoxy composite panels with cutouts and reinforcements aiming at reducing the cutout stress concentration and increasing the buckling stability of the panels. The effect of different cutout sizes and the design and materials of cutout reinforcements on the stress and buckling behaviour of the panels are evaluated. For the sandwich panels with a range of cutout size and a constant weight, an optimal ratio of the core to the face thickness has been studied for the maximum buckling stability. The finite element method and an analytical method are employed to perform parametric studies. In both constant stress and constant displacement shear loading conditions, the results are in very good agreement with those obtained from experiment for selected cutout reinforcement cases. Conclusions are drawn on the cutout reinforcement design and improvement of stress concentration and buckling behaviour of shear loaded laminated and sandwich composite panels with cutouts.
Keywords: Composite sandwich panels; Cutout reinforcements; Monolithic carbon/epoxy plate; Shear loaded